Key Determinants of the Comprehensive Neonatal Emergency Obstetric Services Policy: Penentu Utama Kebijakan Pelayanan Obstetri Darurat Neonatal Komprehensif - Cholifah, Cholifah; Arcellya, Rosalina Septi (Indonesian Journal of Public Policy Review, 2024)
Background: Effective implementation of comprehensive emergency obstetric and neonatal care programs is vital for improving maternal and neonatal health outcomes. Specific Background: At RSU Al-Islam H.M Mawardi, various factors—including communication, resources, disposition, and bureaucratic structure—affect program implementation. Knowledge Gap: Previous research has often neglected how these factors interact and their influence on healthcare policy implementation. Aims: This study evaluates the relationship between these factors and the implementation of the emergency obstetric and neonatal care program using a quantitative survey approach. Results: Analyzing data from 54 respondents revealed significant correlations between effective communication, resource allocation, and successful policy implementation (p < 0.05), with the questionnaire demonstrating high reliability (Cronbach's Alpha = 0.969). Novelty: This research contributes empirical evidence on the specific elements influencing healthcare policy implementation locally. Implications: Strengthening communication and resource management is essential for enhancing policy implementation effectiveness, ultimately improving community health outcomes. Highlights : Factor Influence: Effective communication and resource allocation significantly impact program success. Research Contribution: The study provides empirical evidence on factors affecting healthcare policy implementation locally. Health Outcomes: Strengthening implementation strategies is crucial for improving maternal and neonatal health outcomes. Keywords: obstetric care, neonatal care, policy implementation, communication, healthcare resources